Performance of open-pollinated maize varieties in the drier areas of South-western Nigeria (2011)
The effects of genotype x environment interactions on grain yield of six open-pollinated (OP) maize varieties in two locations within the derived and southern Guinea savanna agroenvironments of southwest Nigeria were investigated using genotype plus genotype x environment interaction (GGE) biplot analysis. Significantly higher grain yields and taller plants were observed at llora (derived savanna) than Ballah (southern Guinea savanna). Grain yields ranged from 1.36 to 3.17 t/ha at Ballah and from 1.59 to 3.27 t/ha at llora. Results of GGE analysis showed that genotype, location and genotype x location interactions accounted for 46.11%, 13.80% and 40.07% of the total variation, respectively. Two of the best yielding varieties, DTSR-Y and ACR 91 Swan 1-SR, were well-adapted to llora environment, while TZB- SR SGY was more suitable for cultivation at Ballah.